2001
DOI: 10.1099/00207713-51-4-1593
|View full text |Cite
|
Sign up to set email alerts
|

Partial sequence analysis of the actin gene and its potential for studying the phylogeny of Candida species and their teleomorphs.

Abstract: The actin gene has been studied as a potential phylogenetic marker for selected members of the anamorphic genus Candida and seven related teleomorphic genera (Debaryomyces, Issatchenkia, Kluyveromyces, Saccharomyces and Pichia from the Saccharomycetaceae ; Clavispora and Metschnikowia from the Metschnikowiaceae). The nucleotide sequences of 36 fungal taxa were analysed with respect to their molecular evolution and phylogenetic relationships. A total of 460 bp (47 %) of the coding 979 bp were variable and 396 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 62 publications
2
40
2
1
Order By: Relevance
“…Previous studies also concluded that these families are monophyletic, albeit with low statistical support (7,21). The combi- (23) were uncertain about the placement of the genera Issatchenkia and Debaryomyces within the Saccharomycetaceae.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies also concluded that these families are monophyletic, albeit with low statistical support (7,21). The combi- (23) were uncertain about the placement of the genera Issatchenkia and Debaryomyces within the Saccharomycetaceae.…”
Section: Discussionmentioning
confidence: 97%
“…(i) Previous studies analyzed single genes and failed to define the relationships among C. albicans, C. viswanathii, C. tropicalis, and C. parapsilosis with significant statistical support (7,14,21,50). This investigation resolved the phylogeny of these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers V9G (de Hoog & Gerrits van den Ende, 1998) and LR5 (Vilgalys & Hester, 1990) were used to amplify the region of the nrRNA gene operon that includes the 39 end of the small-subunit rRNA gene, the ITS regions (ITS 1, ITS 2 and the intervening 5S rRNA gene), and the D1/D2 domain of the large-subunit (LSU) rRNA gene, as described by Knutsen et al (2007). Primers CA14 and CA5R (Daniel et al, 2001) were used to amplify part of the actin gene using the method described by Daniel et al (2001). The PCR products were separated by electrophoresis at 80 V for 40 min on a 0.8 % (w/v) agarose gel containing 0.1 mg ethidium bromide ml 21 in 16 TAE buffer (0.4 M Tris, 0.05 M sodium acetate, and 0.01 M EDTA, pH 7.85) and examined under UV light.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike in euascomycetes, for which a phylogenetic definition of species, phylogenetic species recognition or PSR (Taylor et al, 2000), prevails, the delineation of hemiascomycetous yeasts species has recently been based, in many cases, on the use of rDNA sequence comparison of type strains. A first attempt at using nuclear sequences for this purpose revealed that diversity was much more pronounced than previously thought (Daniel et al, 2001;Daniel & Meyer, 2003). Multigene approaches combining rDNA, housekeeping genes and mitochondrial cytochrome-c oxidase subunit II (COX2) gene sequences have been developed (Kurtzman, 2003;Kurtzman & Robnett, 2003).…”
Section: Introductionmentioning
confidence: 99%